Ownership Structure and Return on Assets of Commercial Bank in Nigeria - Orumo, Joseph Igbiks (American Finance & Banking Review, 2018)
This study examined the effect of ownership structure on return on assets of deposit money banks in Nigeria. The objective was to investigate the relationship between the composition of ownership structure and deposit money banks return on assets. Cross sectional data was sourced from financial statement of fifteen quoted commercial banks. Return on assets was modeled as a function of domestic ownership, ownership concentration, foreign ownership institutional ownership and management ownership. After cross examination of the validity of the pooled effect, fixed effect and the random effect, the study accepts the fixed effect model. The result found that ownership concentration, management ownership and institutional ownership have negative relationship with the dependent variable while private ownership and management ownership have positive relationship with the dependent variable which is return on investment. While private ownership, ownership concentration, institutional ownership and foreign ownership have positive effect on the dependent variable which is return on assets while management ownership have negative effect on the dependent variable. We recommend that regulatory authorities such as the Securities and Exchange Commission, the Nigerian investment promotion council should encourage private investors to invest into the equity shares of the commercial banks and the need for commercial banks to increase their ownership structure through public listing, right issue and other means of attracting public and institutional investors.